APLIKASI TEORI HUMANISTIK ABRAHAM MASLOW DAN AKTUALISASI DIRI DI KALANGAN MAHASANTRI INTENSIF AL-AMIEN PRENDUAN SUMENEP - Redi Irawan; Totok Agus Suryanto (Al-Amien Prenduan for Islamic Institute, 2022)
As a boarding school that is trusted by the wider community and even outside Madura, Al-Amien Prenduan exerts every effort to produce potential and expert students in their respective fields. In this case, the writer observes that Al-Amien Prenduan uses the hierarchy of needs theory initiated by Maslow in order to achieve all his goals and expectations. By using a phenomenological qualitative research approach, the data that the researcher will take comes from the results of interviews with Mahasantri in the form of words and movements of the subject, observations and documents of the boarding school. The researcher intends to reveal the efforts of the Al-Amien Prenduan Islamic boarding school in fulfilling the basic needs of students and the existence of self-actualizing students in the intensive circle of Al-Amien Prenduan, Based on the results of interviews and observations made by researchers to three students who have been manualized, the results of this study reveal that the application of basic student needs fulfillment is very good and satisfying for most students so that researchers find some students who are self-actualizing in the Al-Amien Prenduan boarding school. the characteristics that the researcher will present further in this study.